Take every wave [videorecording (DVD)] : the life of Laird Hamilton - Hamilton, Laird (IFC Films, 2018)
Laird Hamilton is perhaps the greatest big wave surer of all time, a living legend who has tamed some of the world₂s mightiest waves. Amongst the surf community, he is also one of the most controversial figures, an innovator who has revolutionized the sport often to the dismay of purists. This thrilling, up-close portrait traces Hamilton's remarkable journey, from his rebellious childhood in Hawaii to his fearless first forays into surfing to his relentless pursuit of ever-bigger waves.